Changes in management and outcome of patients with rectal cancer in Northern Ireland: 1996–2006. (February 2014) - McClements, J.; Fitzpatrick, D.; Campbell, W. J.; Gavin, A.
Abstract Aim This study aimed to document developments in rectal cancer services in a UK population and evaluate changes in outcome over a 10‐year period. Method Patients diagnosed with primary rectal carcinoma in 1996, 2001 and 2006 were identified by the Northern Ireland Cancer Registry. Data were retrospectively collected on presentation, investigation, treatment and staging. Differences over the period were analysed using the chi‐squared test; Kaplan–Meier and Cox regression tests were used for survival analysis. Results After exclusions there were 636 patients, including 187 presenting in 1996, 203 in 2001 and 246 in 2006. The use of preoperative MRI of the rectum, endorectal ultrasound and abdominal CT increased during the study period. For patients treated by surgery, total mesorectal excision (TME) increased from 19% in 1996 to 64% in 2006 (P < 0.001). The use of radiotherapy (27% in 1996, 47% in 2006) and chemotherapy (21% in 1996, 32% in 2006) increased. The overall 5‐year survival improved significantly between 1996 and 2006 from 34% in 1996 to 45% in 2006 (P = 0.02). Among patients having surgery, 5‐year survival increased from 43% in 1996 to 63% in 2006 (P < 0.001). Multivariate analysis showed that the improvement in survival was associated with TME and chemotherapy, while radiotherapy was not. Conclusion Survival of patients with rectal cancer in Northern Ireland has improved significantly over the last decade, probably due to the increased use of TME and chemotherapy.